Violence and apocalyptic notions in Mark 13 - Hombana, Mphumezi (Hervormde teologiese studies, 2024)
Mark 13 is famously known as the most challenging text in the entire Markan gospel. In Mark 13:7–8, the Markan Jesus foretells a tumultuous period marked by wars, rumours of wars, nations in conflict and natural hazards, aligning with common motifs in apocalyptic literature. The language vividly depicts a world in upheaval, emphasising cosmic and earthly disturbances as harbingers of climactic historical moments. The destruction of the temple, announced in Mark 13:2, is subject to both literal and symbolic interpretations, with some associating it with the historical event of the Second Temple’s destruction in 70 CE and others perceiving it as a symbol of the end of an age. Approaching Mark 13 without being triggered by violent connotations is unthinkable. Hence, responsible interpretation is pivotal in addressing such potentially violent connotations, particularly considering contemporary world conflicts. Sensitivity, without compromising the truth of the message of Mark 13, is crucial when considering the text’s impact on war-torn communities. This applies both to a reading that simulates the possible intention of the text within the context in which the Gospel, according to Mark, originated and to a historically informed use of such a reading considering contemporary conflicts. This study aims to employ a historiographical hermeneutic as an investigative tool to contribute a plausible understanding of the present text and avoid utilising this text as proof to promote violence and wars today. Especially, when one considers the recent catastrophes: natural hazards, civil unrest and wars across the world. Some are quick to utilise the Olivet discourse to explain such gruesome activities.ContributionThis study contextualizes Mark 13 within the 1st century CE, focusing on the Second Temple’s destruction in 70 CE. It promotes a sensitive interpretation, avoiding justifications for contemporary violence, and highlights the text’s relevance by drawing parallels between its turmoil and current global conflicts, encouraging ethical reflection.